Armitage [videorecording (DVD)] : dual-matrix - Akiyama, Hatsuhito; Lewis, Juliette; Stellrecht, Skip; Forstadt, Rebecca (Pioneer, 2002)
Naomi Armitage and Ross Sylibus have changed their names and live with their daughter Yoko as a normal happy family on Mars--until a robot riot breaks out at an anti-matter plant on Earth. Armitage learns the riot is a plot to suppress illegal research and development of more "Third Robots" and decides to go to Earth to find out who is behind it. What Armitage discovers is the most powerful enemy she has ever encountered--replicas of herself.